The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.5402/2012/916845
|View full text |Cite
|
Sign up to set email alerts
|

Use of Probiotics in Aquaculture

Abstract: The growth of aquaculture as an industry has accelerated over the past decades; this has resulted in environmental damages and low productivity of various crops. The need for increased disease resistance, growth of aquatic organisms, and feed efficiency has brought about the use of probiotics in aquaculture practices. The first application of probiotics occurred in 1986, to test their ability to increase growth of hydrobionts (organisms that live in water). Later, probiotics were used to improve water quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
188
1
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 370 publications
(201 citation statements)
references
References 95 publications
4
188
1
8
Order By: Relevance
“…They could improve growth performance and feed conversion efficiency of fish by producing short chain fatty acids, digestive enzymes and vitamins (Martínez et al, 2012), enhance immune response by effecting T-cell differentiation ( Merrifield et al, 2010), provide resistance to pathogenic organisms ( Muñoz-Atienza et al, 2013) and increase tolerance under stressful condition (Varela et al, 2010). Moreover, also assure the digestion of anti-nutritional factors (Suzer et al, 2008), enhance fish appetite, improve carcass and flesh quality (van Nuenen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…They could improve growth performance and feed conversion efficiency of fish by producing short chain fatty acids, digestive enzymes and vitamins (Martínez et al, 2012), enhance immune response by effecting T-cell differentiation ( Merrifield et al, 2010), provide resistance to pathogenic organisms ( Muñoz-Atienza et al, 2013) and increase tolerance under stressful condition (Varela et al, 2010). Moreover, also assure the digestion of anti-nutritional factors (Suzer et al, 2008), enhance fish appetite, improve carcass and flesh quality (van Nuenen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, prevention and control of animal diseases has focused on the use of chemicals and antibiotics, which generate significant risks to public health by promoting the selection, propagation, and persistence of bacterial-resistant strains (FAO,2006 andWHO, 2012). Probiotics are considered as safe and viable alternatives for the health management for improved production in aquaculture (Martinez et al, 2012). Recent studies have shown the presence of genes that confer antibiotic resistance thereby posing a danger of transmission of such genes to pathogenic bacteria through horizontal gene transfer (Imperial et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, since the freshly hatched larvae do not have microbial community in the gut, on the gills or on the skin, they become more susceptible to the diseases caused by pathogens. In this respect, application of potent extracellular enzyme-producing autochthonous bacteria might hold promise to provide nutritional support and limit pathogenic microbial load to reduce mortality in catfish larvae as indicated for probiotic applications elsewhere (Cruz et al 2012).…”
Section: Introductionmentioning
confidence: 99%